Presolar stardust in highly pristine CM chondrites Asuka 12169 and Asuka 12236. (18th January 2021) - Nittler, Larry R.; Alexander, Conel M. O'D.; Patzer, Andrea; Verdier‐Paoletti, Maximilien J.
Abstract: We report a NanoSIMS search for presolar grains in the CM chondrites Asuka (A) 12169 and A12236. We found 90 presolar O‐rich grains and 25 SiC grains in A12169, giving matrix‐normalized abundances of 275 (+55/−50, 1σ) ppm or, excluding an unusually large grain, 236 (+37/−34) ppm for O‐rich grains and 62 (+15/−12) ppm for SiC grains. For A12236, 18 presolar silicates and 6 SiCs indicate abundances of 58 (+18/−12) and 20 (+12/−8) ppm, respectively. The SiC abundances are in the typical range of primitive chondrites. The abundance of presolar O‐rich grains in A12169 is essentially identical to that in CO3.0 Dominion Range 08006, higher than in any other chondrites, while in A12236, it is higher than found in other CMs. These abundances provide further strong support that A12169 and A12236 are the least‐altered CMs as indicated by petrographic investigations. The similar abundances, isotopic distributions, silicate/oxide ratios, and grain sizes of the presolar O‐rich grains found here to those of presolar grains in highly primitive CO, CR, and ungrouped carbonaceous chondrites (CCs) indicate that the CM parent body(ies) accreted a similar population of presolar oxides and silicates in their matrices to those accreted by the parent bodies of the other CC groups. The lower abundances and larger grain sizes seen in some other CMs are thus most likely a result of parent‐body alteration and not heterogeneity in nebular precursors. Presolar silicates are unlikely to be present in high abundances in returned samples from asteroids Ryugu and Bennu since remote‐sensing data indicate that they have experienced substantial aqueous alteration.